Seven fundamental rethinking for next-generation wireless communications. (20th September 2017) - I, Chih-Lin
Abstract : The fifth-generation (5G) mobile communication networks, which are anticipated to be soft, green, and super-fast, may possibly be deployed in 2020s to satisfy the challenging demands of mobile communication in various scenarios. Characterized by a mixed set of key performance indicators like data rates, latency, mobility, energy efficiency, and traffic density, 5G services demand a fundamental revolution on the end to end network architecture and key technologies design. Toward a "soft, green, and super-fast" 5G, this paper presents seven innovative 5G R&D themes of China Mobile, including: (1) rethinking Shannon to start a green journey on wireless systems; (2) rethinking Ring and Young for no more "cells"; (3) rethinking signaling and control to make network applications aware and load aware; (4) rethinking antennas to make base stations invisible via SmarTiles; (5) rethinking spectrum and air interface to enable wireless signals to "dress for the occasion"; (6) rethinking fronthaul (FH) to enable Soft RAN via next-generation FH interface; and (7) rethinking the protocol stack for flexible configurations of diversified access points and optimal baseband function split between the base band unit pool and the Remote Radio Systems.